Formal and informal support of family caregivers managing medications for patients who receive end-of-life care at home: A cross-sectional survey of caregivers. (October 2014) - Joyce, Brian T; Berman, Rebecca; Lau, Denys T
Background: Managing medications is a complex responsibility of family caregivers caring for end-of-life patients. This study characterizes caregivers with and without formal/informal support managing medications for patients who receive end-of-life care at home. Aim: To explore factors related to caregivers' support with managing medications for end-of-life home hospice patients. Design: A convenience-sampled, cross-sectional telephone survey. Setting/participants: Computer-assisted telephone interviews were administered to 120 caregivers managing medications, who were referred by five Chicago-based home hospice services. We measured caregivers' additional formal (paid) and informal (unpaid) support with managing medications, and caregiver/patient socio-demographic, relational, and health characteristics. Results: While 47 (39%) had no additional support with managing medications, 27 (22.5%) had formal support, 37 (31%) informal, and 9 (7.5%) both. Seven caregivers (19%) with formal and 13 (31%) with informal support reported disagreements concerning treatment plans. Caregivers lacking formal support tended to be racial/ethnic minorities, live with the patient in their home, or report greater emotional burden. Caregivers with formal support tended to report higher education/income, lower mutuality, or care for a patient with over 6 months' hospice enrollment. Caregivers lacking informal support tended to be spousal caregivers, live with the patient, or have experience caring for another dying person. Conclusion: Our study suggests that high proportions of caregivers may not have support managing medications for patients receiving hospice care at home. More research should examine whether the observed variations in obtaining support indicate disparities or unmet needs among caregivers. Disagreement about treatment with formal/informal support also warrants further investigation.